2013
DOI: 10.1371/journal.pone.0071833
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Seroconversion by Leishmania infantum in a Cohort of Dogs from an Endemic Area of Brazil

Abstract: Visceral leishmaniasis (VL) has recently emerged in various urban and peri-urban areas of Brazil and other countries. Understanding the urbanization of VL requires identification of risk factors associated with human and canine infection. To determine the predictors of risk for canine VL, a survey was conducted of 1,443 dogs, from which a cohort was selected (n = 455) and evaluated for approximately 26 months. Serology was conducted with two enzyme-linked immunosorbent assays (ELISA): one conducted in the Labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 49 publications
1
37
1
3
Order By: Relevance
“…Epidemiological studies indicate that the infection is associated with particular risk factors such as the length of an animal's coat, the areas in the house frequented by the dog 4 , and the socioeconomic and demographic indicators of the region 5 . The aim of this study was to determine the seroprevalence of CVL in urban and rural areas by identifying the risk factors involved in the transmission of this disease in the municipality of Jaciara, State of Mato Grosso.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies indicate that the infection is associated with particular risk factors such as the length of an animal's coat, the areas in the house frequented by the dog 4 , and the socioeconomic and demographic indicators of the region 5 . The aim of this study was to determine the seroprevalence of CVL in urban and rural areas by identifying the risk factors involved in the transmission of this disease in the municipality of Jaciara, State of Mato Grosso.…”
mentioning
confidence: 99%
“…Short-coated dogs have twice the risk of infection as longhaired dogs because the protection afforded by long hair hinders biting by phlebotomines 4 ; In fact, all dogs in the rural areas were had short coats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Así, la presencia de árboles, el manejo de residuos orgánicos y la percepción de la calidad de los servicios públicos no mostraron una asociación con el riesgo de la leishmaniasis visceral humana. Estas condiciones se han asociado a la abundancia de vectores en Posadas (9,10), mientras que en un foco de Brasil, la infección asintomática por L. infantum en humanos se asoció positivamente con la ausencia de residuos (35).…”
Section: Discussionunclassified
“…During such periods, B lymphocytes do not secrete polyclonal antibodies, and consequently, serological methods are less sensitive at this stage of infection (30,31). Moreover, it has been observed that these dogs are more likely to seroconvert than are PCR-negative dogs (32). Vaccines against CVL have been promoted as an important tool and a cost-effective strategy for controlling the disease (33).…”
Section: Discussionmentioning
confidence: 99%